A pilot study of chromosomal aberrations and epigenetic changes in peripheral blood samples to identify patients with melanoma. Issue 5 (October 2015) - Jakub, James W.; Grotz, Travis E.; Jordan, Philip; Hunter, Ewan; Pittelkow, Mark; Ramadass, Aroul; Akoulitchev, Alexandre; Markovic, Svetomir
<x xml:space="preserve">Abstract</x> Prognosis is markedly improved when melanoma is diagnosed early. Improved methods are needed for earlier detection and screening. We hypothesized that epigenetic analysis of blood samples could discriminate patients with melanoma from patients with other cutaneous lesions and from healthy volunteers. After institutional review board approval and consent, whole blood was obtained from 59 patients with melanoma, 20 patients with other skin cancers, 20 patients with benign skin conditions, and 20 healthy volunteers. Fifteen conformation biomarkers from five gene loci were analyzed on chromatin with the EpiSwitch technology using a modified chromatin conformation capture assay. Differentiation between patients with melanoma and those with nonmelanoma skin cancers was correct 85% of the time, resulting in a sensitivity of 88% and a specificity of 82%. Differentiation of patients with melanoma from healthy controls was correct 80% of the time, resulting in a sensitivity of 85% and a specificity of 75%. The noninvasive test was more accurate in early-stage melanoma (1/10 and 1/16 stage I and stage II patients were misclassified, respectively) and became less accurate with more advanced disease (3/14 and 4/19 stage III and IV patients were misclassified, respectively). We report the results of a noninvasive test using chromosomal aberrations and epigenetic changes identified in peripheral blood that, in this pilot study, distinguished patients with early-stage melanoma from other cohorts.